2022
DOI: 10.3390/agronomy12071702
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Fluorescence and Fruit Quality Response of Blueberry to Different Mulches

Abstract: Mulch is widely used in blueberry cultivation for weed control; however, there is still uncertainty as to how the use of different types of mulch alters leaf photosynthetic behavior and the quality and productivity of blueberry fruit. The objective of our research was to evaluate the effect of different types of mulch on the physiological, quality and yield characteristics of blueberries. Three treatments were established: T1 (control), T2 (pine bark) and T3 (geotextile) in two cultivars: Ochlockonee and Legac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Similar to the results of this study, Strike and Davis [32] reported that blueberry diameter and firmness were unaffected by the mulch type. Retamal-Salgado et al [37] also reported that the use of pine bark and geotextiles as mulch in blueberries only increased fruit yield without affecting fruit firmness and other fruit qualities. Whilst Pliszka et al [38] observed significant influences of mulches on the growth and yield of blueberry fruits, a study by Krewer et al [39] showed minimal impacts of mulch application in the first year.…”
Section: Mulching Effects On Fruit Yield and Qualitymentioning
confidence: 97%
“…Similar to the results of this study, Strike and Davis [32] reported that blueberry diameter and firmness were unaffected by the mulch type. Retamal-Salgado et al [37] also reported that the use of pine bark and geotextiles as mulch in blueberries only increased fruit yield without affecting fruit firmness and other fruit qualities. Whilst Pliszka et al [38] observed significant influences of mulches on the growth and yield of blueberry fruits, a study by Krewer et al [39] showed minimal impacts of mulch application in the first year.…”
Section: Mulching Effects On Fruit Yield and Qualitymentioning
confidence: 97%
“…Maximum fluorescence intensity (F m ) and minimum fluorescence intensity (F 0 ) of chlorophyll were measured with a portable fluorimeter model OS-30p (Opti-Sciences) on fully sun-exposed leaves, mature and annual shoots located in the second third of the shoot, considering a total of 18 measurements per treatment [30,31], at five times of the day, 09:00, 11:00, 13:00, 15:00, 17:00 h, during a clear day. These results allowed quantification of the maximum photochemical efficiency of photosystem II (F v /F m ) [32,33].…”
Section: Plant Physiological Parametersmentioning
confidence: 99%
“…Immediately after harvest, fruit firmness and equatorial diameter were determined using FirmPro equipment (Happy Volt SPA, Santiago, Chile) [28,31,34]. Firmness was expressed as the force in grams (g) necessary to deform the fruit in 1 mm (gf mm −1 ).…”
Section: Yield and Physical-chemical Parameters Of Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic mulching (PM) has been reported as a way of minimizing salt accumulation in the soil [23,24] and, consequently, toxicity to plants caused by irrigation water [7,25]. The use of mulching in arid and semiarid regions has been increasingly employed in agriculture as it maintains soil moisture at high levels and reduces temperature [26][27][28], especially in places where the only water source available shows considerable concentrations of soluble salts [29]. According to [30] Aragüés et al (2014), plastic mulching reduces the need for frequent irrigation as it prevents water loss through evaporation into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%